Temporal provisions of the bankruptcy doctrine - E. V. Liubimova; M. G. Sukhanova (Правоприменение)
In the context of the burgeoning Russian insolvency law, the applicable regulations may undergo essential changes over a bankruptcy period due to lengthy insolvency procedures. In such case, a pivotal question for the bankruptcy participants is the application of legal developments that significantly affect the participants’ scope of rights and obligations to the initiated procedure.This study is aimed to develop and substantiate a unified procedure for the commencement of legal provisions governing the bankruptcy procedure.The following tasks promote the above purpose:1) Determining applied options of commencement of amendments to the Insolvency Law;2) Weighing strengths and weaknesses of the determined options;3) Concluding on the most suitable procedure for commencement of amendments in these legal relationships.The analysis of amendments to the Insolvency Law highlights the absence of a legislator’s unified approach. The article outlines seven models of amendments commencement used by the legislator:1) amendments to the Insolvency Law do not describe the commencement procedure, so the general rule applies here: entry into force after ten days upon the date of their official publication;2) amendments to the Insolvency Law explicitly specify the date of entry into force or the period on the expiry of which the amendments enter into force;3) amendments to the Insolvency Law enter into force on the day of their official publication;4) amendments to the Insolvency Law apply in bankruptcy cases in which proceedings are initiated after the date of the amendments commencement;5) amendments to the Insolvency Law single out a cluster of legal relationships (e.g. legal relationships in current costs accounting) to which the amendments apply immediately (which is an exception to the general term of amendments commencement);6) amendments to the Insolvency Law specify legal facts, given which a new version of the law shall or shall not apply; in particular, the legislator has used the following jural facts (1) the beginning of settlements with creditors of the third priority; (2) the completion of a monitoring procedure in relation to an indebted developer;7) amendments to the Insolvency Law imply an extension of new rules to earlier existing legal relationships.Following the analysis of strengths and weaknesses of the given models the authors believe that a new legal regulation (if any) shall be recognized when the bankruptcy case moves from one procedure to another. At the date of transition, the current version of the law in force is determined, its reference indicated in the judicial act. This mechanism allows the parties to the legal relationship to know with certainty the legal assessment from the judicial act and to build on the new legal regulation in their line of conduct. In the event of a fundamental change in the law, the parties will be protected by the current procedure as a temporary safeguard.This will make the bankruptcy procedure foreseeable for the parties and prevent unpredictable risks that did not exist at the initiation of the bankruptcy proceedings.